2022
DOI: 10.1039/d2nh00281g
|View full text |Cite
|
Sign up to set email alerts
|

Tuning photoelectron dynamic behavior of thiolate-protected MAu24 nanoclusters via heteroatom substitution

Abstract: Heteroatom substitution of gold nanoclusters enables precise tuning of their physicochemical properties at single-atom level, which has importance impact on the applications related to excited states including photovoltaic, photocatalysis and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 66 publications
1
26
0
Order By: Relevance
“…The participation of Ag(sp) and M(sp) orbitals in the PtAg 24 NCs is obviously less pronounced than that in PdAg 24 and AuAg 24 NCs, this result is in accordance with the relatively shorter M-Ag bond lengths among the doped NCs (Table 1). [46] A similar phenomenon could also be found in the LUMOs of the NCs, the contribution of Pt(5d) is less pronounced than the other two doped NCs, which indicates weaker d-d hybridization between Pt and the Ag atoms in PtAg 24 NCs. Ag 25 , PdAg 24 , and AuAg 24 exhibit similar band structures with closed HOMO and LUMO positions.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…The participation of Ag(sp) and M(sp) orbitals in the PtAg 24 NCs is obviously less pronounced than that in PdAg 24 and AuAg 24 NCs, this result is in accordance with the relatively shorter M-Ag bond lengths among the doped NCs (Table 1). [46] A similar phenomenon could also be found in the LUMOs of the NCs, the contribution of Pt(5d) is less pronounced than the other two doped NCs, which indicates weaker d-d hybridization between Pt and the Ag atoms in PtAg 24 NCs. Ag 25 , PdAg 24 , and AuAg 24 exhibit similar band structures with closed HOMO and LUMO positions.…”
Section: Resultssupporting
confidence: 59%
“…Moreover, the LUMO + 1 orbital of Ag 25 NCs exhibits diffuse superatomic d‐type orbitals, where strong hybridization would occur among the interfacial atoms and thus facilitate the transfer of photoinduced electrons in space, further contributing to the electron–hole pairs separation. [ 46 ] Therefore, it could be concluded that the improved charge separation in Ag 25 /TiO 2 leads to greatly enhanced photocatalytic activities compared to the bare TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17][18] Based on the new knowledge acquired, researchers can customize nanomaterials more rationally, and cluster-based nanomaterials will find new opportunities in a wide range of applications, such as catalysis, chemical sensing, biological imaging, chirality, two-photon absorption, energy storage, and nanoelectronics. [19][20][21][22][23][24][25][26][27][28][29] Nanoresearch is designed to employ nanoparticles/nanoclusters or their aggregates as complex entities to realize certain functions. Bulk metals are chemically inert and antioxidized, while metal nanoclusters such as Au nanoclusters, 30,31 Ag nanoclusters, [32][33][34][35] and alloy nanoclusters [36][37][38] are relatively unstable and chemically reactive.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these preliminary achievements, the fundamental understanding of these fascinating Janus heterostructures, especially for the underlying mechanisms of excited-carrier relaxation and recombination, remains unknown. In recent years, based on time-dependent ab initio nonadiabatic molecular dynamics (NAMD), , it has become possible to achieve valuable insights into the photogenerated carrier dynamics in many structures, including 2D monolayer semiconductors, heterostructure interfaces, and halide perovskites. , Inspired by this, we chose Janus TMDs heterostructures including vertical and lateral heterostructures formed by MoSSe and WSSe monolayers (see Figure ), as templates to explore the photoinduced excited-dynamic behavior of Janus heterostructures. The photoinduced carrier transfer pathways, hot carrier relaxation, and electron–hole recombination dynamics at MoSSe/WSSe interfaces reveal important insights that could provide a detailed atomistic understanding of ultrafast charge carrier dynamics, proving integral for the optimal design of high-performance heterostructures for nanoelectronics, optoelectronics, and photocatalytic devices in the future.…”
Section: Introductionmentioning
confidence: 99%